Mediation Model of Factors Affecting Continuous Use of M-government Services of Abu Dhabi Smart City - Safiah Sidek; Ali Alkaabi, Saqr Khalfan; Abo Mosali, Najmaddin (International Journal of Sustainable Construction Engineering and Technology, 2022)
This paper presents a development of mediation model using SEM-AMOS software. The model hypothesized that the direct relationship is between the quality and public value constructs with continuous intention to use M-government services. While, the mediator constructs to the direct relationship are trust and satisfaction constructs. The data used to develop and testing this model was gathered through questionnaire survey from 231 valid responses from Abu Dhabi smart city residents using the police department M-services. The development of the model was conducted in two stages where at first stage it involved confirmatory factor analysis and the second stage involved path analysis. The analysis on the model found that quality construct has significant direct relationship with trust and user satisfaction constructs, but it does not have significant direct relationship with continuous to use construct. Similarly, the public value construct has significant direct relationship with trust and user satisfaction constructs, but it does not have significant direct relationship with continuous intention to use construct. Thus, both the user satisfaction and trust constructs have a full mediation effect with the direct relationship of public value and quality construct with continuous intention to use construct of M-government services. Thus, it can be concluded that the relationship of public value and quality constructs with continuous to use construct is fully mediated by both trust and satisfaction constructs in M-government services. The findings from this study assists the government for continuous usage of M-government services that contributes to the sustainability of smart city.